Writing double : women's literary partnerships - London, Bette Lynn. (Ithaca : Cornell University Press, 1999)
Annotation Although Roland Barthes and Michel Foucault announced the death of the author several decades ago, critics have been slow to abandon the idea of the solitary writer. Bette London maintains that this notion has blinded us to the reality that writing is seldom an individual activity and that it has led us to overlook both the frequency with which women authors have worked together and the significance of their collaborative undertakings as a form of professional activity. In Writing Double, the first full-length treatment of women?s literary partnerships, she goes to the heart of issues surrounding authorial identity. What is an author? Which forms of authorship are sanctioned and which forms marginalized? Which of these forms have particularly attracted women? Such questions are central to London?s analysis of the challenge that women?s literary collaboration presents to accepted notions of authorship. Focusing on British texts from the nineteenth and twentieth centuries, she considers a fascinating variety of works by largely noncanonical, and in some instances highly unconventional, authors--from the enormously popular novels composed by writing teams at the turn of the century, to the Bront? juvenilia and the occult scripts of Georgie Yeats and W.B. Yeats, to automatic writings produced by mediums purporting to be in communication with the spirit world.
1. Secret Writing: The Bronte Juvenilia and the Myth of Solitary Genius -- 2. "Something Obscurely Repellent": The Resistance to Double Writing -- 3. Two of a Trade: Partners in Writing, 1880-1930 -- 4. Writing at the Margins: Collaboration and the Discourse of Exoticism -- 3. The Scribe and the Lady: Automatic Writing and the Trials of Authorship -- 6. Romancing the Medium: The Silent Partnership of Georgie Yeats -- Afterword: Ghostwriting; or, The Afterlife of Authorship.
Includes bibliographical references and index.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
Print version record.
JSTOR
Keywords: English literature -- Women authors -- History and criticism; Women and literature -- Great Britain -- History -- 19th century; Women and literature -- Great Britain -- History -- 20th century; Authorship -- Collaboration -- History; Spirit writings -- Authorship; Women mediums -- Biography; Écrits de femmes anglais -- Histoire et critique; Femmes et littérature -- Grande-Bretagne -- Histoire -- 19e siècle.; Femmes et littérature -- Grande-Bretagne -- Histoire -- 20e siècle.; Coauteurs -- Histoire; Écrits spirites -- Art d'écrire.; Femmes médiums -- Biographies; LITERARY CRITICISM / Women Authors; Authorship -- Collaboration; English literature -- Women authors; Women and literature; Women mediums; Great Britain; Mitverfasser; Literaturproduktion; Partnerschaft; Kooperation; Frauenliteratur; Literatur; Schriftstellerin; Großbritannien; Frau -- Kollektive Autorschaft -- englische -- Geschichte 19. Jh; Kollektive Autorschaft -- englische -- Frau -- Geschichte 19. Jh; Schriftstellerin -- Grossbritannien -- Kooperation -- Geschichte -- 1800-1930.; Kooperation -- Schriftstellerin -- Grossbritannien -- Geschichte -- 1800-1930.; Autorschaft -- Frau -- Kooperation -- Geschichte -- 1800-1930.; Kooperation -- Frau -- Autorschaft -- Geschichte -- 1800-1930.; Frau -- Autorschaft -- Kooperation -- Geschichte -- 1800-1930.; Englisch; 1800-1999; Biographies; Criticism, interpretation, etc; History